Spatial Dynamics of a Phlebotomine Sand Flies Population in Response to Climatic Conditions in Bushehr Province of Iran - Zahra Zarei Cheghabaleki; Dariush Yarahmadi; Mostafa Karampour; Aliakbar Shamsipour (Ubiquity Press, 2019)
Background: Phlebotomine (Ph.) sand flies are the vectors of different types of leishmaniasis and arboviruses to humans. Variations in climate conditions could lead to changes in the dynamics of zoonotic cutaneous leishmaniasis (ZCL) and its agents, such as Ph. sand flies and reservoirs. Objective: The aim of this study was to analyze the spatial relationship among climatic factors and phlebotomine sand flies in abundance in Bushehr Province of Iran. Materials and Methods: In this study, six village sites in Bushehr Province were selected for collecting Ph. sand flies. All-night landing catches of Ph. sand flies occurred between January 15, 2016, and December 15, 2016. Two types of climatic data were used: satellite-based data included daytime and nighttime land surface temperature and the normalized deference vegetation index, and station-based data included annual rainfall and annual mean air temperature and solar radiation (W/M2). Spatial correlation analysis and multivariate ordinary least square regression was used to detect the spatial association between caught Ph. sand flies and climatic factors in a 0.95 confidence level (p = 0.05). Results: The results of the spatial correlation matrix indicated thermal factors, such as mean and maximum air temperature, instantaneous daytime and nighttime land surface temperatures, and radiation, show a direct and significant spatial correlation with the number of sand flies caught. The annual frequency of sand flies in the region showed the highest direct spatial relationship with the annual maximum air temperature (r = 0.91). Environmental moisture factors, such as precipitation and the vegetation index of the region, have spatial correlations of 0.63 and 0.44 with the frequency of the annual caught sand flies, which are significant at the confidence level of 0.95. The results of the multivariable model for estimating the frequency of the caught sand flies indicate environmental estimators, including mean air temperature, rainfall, radiation, and vegetation index, in a linear estimation model can explain the 0.85 spatial variation of the caught sand flies population. This study aimed to detect spatial correlations between the sand fly population and climatic factors. The results showed climatic factors were the most important controllers of the sand fly population in the interannual scale. If sand fly control programs are conducted in accordance with the climatic conditions of the area, the population of this carrier in Bushehr Province can be controlled and the incidence of disease significantly reduced.